Vaginal bleeding during pregnancy and adverse pregnancy outcomes: a nationwide population-based retrospective cohort study in Iran - Mina Tahmasebifard; Sima Afrashte; Mahmoud Hajipour; Behnam Zamani; Shahab Rezaeian (BMC Pregnancy and Childbirth)
Abstract Background Vaginal bleeding (VB) as a common pregnancy problem affects approximately one fourth of pregnancies and leads to abortion in 50% of cases. The occurrence of vaginal bleeding during pregnancy heightens the probability of experiencing diverse adverse pregnancy outcomes. The existing scientific research regarding the relationship between vaginal bleeding and adverse pregnancy outcomes in Iranian women is restricted and presents conflicting findings. Consequently, this research examines the association of vaginal bleeding during pregnancy and unfavorable outcomes in Iranian women. Methods This population based retrospective cohort study was conducted in 11 provinces of Iran. The necessary data were collected using the questionnaires and medical records from 3634 pregnant women. The association between vaginal bleeding and stillbirth, premature birth, low birth weight, premature membrane rupture of the membranes (PPROM), gestational diabetes, and pre-eclampsia was done using univariable and multivariable logistic regression. Results The prevalence of vaginal bleeding has a declining trend based on BMI and birth cohort of women. Multivariable logistic regression showed that the odds of low birth weight (OR = 1.52, 95%CI: 1.04–2.24), PPROM (OR = 2.12, 95%CI: 1.19–3.76), preterm birth (OR = 1.74, 95%CI: 1.19–2.56), and stillbirth (OR = 2.10, 95%CI: 1.59–2.77) are significantly higher in women who experience vaginal bleeding during pregnancy in compared to women who do not have vaginal bleeding. Conclusions Although a declining trend of vaginal bleeding was found, these findings indicate an increased risk of stillbirth, preterm birth, and low birth weight due to VB. Educational interventions to prevent adverse pregnancy outcomes among high-risk women are suggested.